Exploring Therapeutic Potential of Bi-Qi Capsules in Treatment of Gout by Discovering Crucial Drug Targets - Jing Xie; Yu Zhang; Rong Ren; Ruizhen Bu; Liying Chen; Juezhuo Hou; Dandan Shang; Yadong Liu; Dan Wang; Tao Wang; Hong Zhou (Pharmaceuticals)
Objectives: This research aims to explore the therapeutic potential of Bi-Qi capsules in the treatment of gout by identifying crucial drug targets through a multidimensional data analysis strategy. Methods: Bi-Qi capsule drug targets and differentially expressed genes (DEGs) of gout were derived from public databases, such as Swiss Target Prediction, STITCH, and the GEO database. Subsequently, the overlapped targets were analyzed to elucidate the potential therapeutic mechanism and to identify candidate targets of Bi-Qi capsules against gout. Next, Mendelian randomization (MR) analysis was employed to screen and explore the causal relationship between candidate targets and gout. Finally, single-cell RNA sequencing (scRNA-seq), gene set enrichment analysis (GSEA), transcription factor and ceRNA regulatory networks, and molecular docking were performed to validate the role of the crucial targets of Bi-Qi capsules in the treatment of gout. Results: A total of 46 candidate targets were identified, in which KCNA5, PTGS2, and TNF exhibited significant causal relationships with gout (p < 0.05) and were regarded as the crucial targets. Through scRNA-seq and gene labeling, crucial targets were found to be expressed in eighteen cell clusters and eight cell types, which are closely associated with carbohydrate metabolism, nerve conduction, and the innate immunity process. Bi-Qi capsule active compounds such as tanshinone IIA, strychnine, tanshinaldehyde, cryptotanshinone, tumulosic acid, and glycyrrhetic acid exhibit a better binding ability to crucial targets. Conclusions: The results not only elucidate the anti-gout mechanism of Bi-Qi capsules but also provide an insight into multi-target natural medication for metabolic disease treatment, which contributes to guiding the clinical application of Bi-Qi capsules in the future.